(untitled) (Global Journal of Human-Social Science, 2024)
There are collective behaviors that lead violence one of these is lynching It is a type of violence where mimesis act in all its power In fact when the crowd unites to exert violence on one it tends to imitate the aggressiveness that arises in the other they are all infected by the same feeling to persecute and lynch a subject who is criminalized by the group and is symbolized as the source of evil since he is the catalyst of common bewilderment Our interpretative bet is developed in three moments First we will make a general presentation of the theory of mimetic desire proposed by Ren Girard From there we are interested in describing the motivational inputs that feed a conception of violence and that will have a foothold in the sacrificial mechanism In a second moment we will conceptualize the theory of sacrifice and its relationship with the sacred emphasizing the idea of the crowd and lynching Finally we will address from a literary interpretation the phenomenon of violence sacrifice and lynching that is recreated in the novel 2666 by Roberto Bola o